2020
DOI: 10.1080/10426507.2020.1828886
|View full text |Cite
|
Sign up to set email alerts
|

New spirothiazolidinone derivatives: Synthesis and antiviral evaluation

Abstract: A new series of N-(3-oxo-1-thia-4-azaspiro[4.5]decan-4-yl)carboxamide derivatives were designed, synthesized, and evaluated for their antiviral activity. These new spirothiazolidinone compounds (3a-f, 4a-f) were prepared by a cyclocondensation reaction of hydrazides (1, 2) and appropriate ketones with 2-sulfanylpropionic acid. All compounds were characterized by IR, 1 H NMR, and elemental analysis. N-(8-Ethyl-2-methyl-3-oxo-1-thia-4-azaspiro[4.5]decan-4-yl)-4-methylbenzamide (3c) and 4-methyl-N-(2-methyl-3-oxo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Antiviral activity of compounds 63 against influenza A and B viruses and human coronaviruses 229E strain was published by Apaydın et al [48]. 63a and 63b have shown satisfactory inhibition of influenza A/H 3 N 2 (EC 50 = 1.4, 0.80).…”
Section: Biological Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Antiviral activity of compounds 63 against influenza A and B viruses and human coronaviruses 229E strain was published by Apaydın et al [48]. 63a and 63b have shown satisfactory inhibition of influenza A/H 3 N 2 (EC 50 = 1.4, 0.80).…”
Section: Biological Activitymentioning
confidence: 99%
“…Apaydın et al [48] reported the preparation of a novel azaspiro-carboxamides 63 and 65. The hydrazines 62 and 64 were refluxed with appropriate cyclohexanone 44 and S C H E M E 1 2 Synthesis of novel bis-pyrimidinyl-spiro-4-thiazolidinones 2-sulfanylpropanoic acid 3 in toluene to furnish corresponding spirothiazolidinones (Scheme 16).…”
Section: Conventional Synthesismentioning
confidence: 99%
“…[ 8 ] For the lead compound, A1 , the average EC 50 for different strains of human influenza A/H3N2 was 9.6 µM and the IC 50 (cytostatic activity) was 93 µM, yielding a selectivity index of 10. Subsequent structure–activity relationship (SAR) analyses demonstrated that antiviral efficacy and selectivity show no drastic change when the aromatic part is replaced by 1‐adamantyl ( A2 ), [ 9 ] 5‐chloro‐2‐hydroxy/methoxyphenyl ( A3 ), [ 10,11 ] 4‐chlorophenoxymethyl ( A4 ), [ 12 ] or 2‐methylfuran‐3‐yl ( A5 ) [ 13 ] (Figure 1). The compounds were proven to act as influenza A/H3N2 virus fusion inhibitors by hindering the conformational change of the viral hemagglutinin (HA) at low pH, a process required to provoke the fusion of the viral envelope and endosomal membrane.…”
Section: Introductionmentioning
confidence: 99%